English Language Ability and the Labor Market Opportunities of Hispanic and East Asian Immigrant Men - Kossoudji, Sherrie A. (Journal of Labor Economics, 1988)
Immigrant workers will be evaluated by their ability to speak English as well as by their other skills. The empirical work in this article add resses the hypothesis that there is an economic cost to English langu age deficiency both in occupation-specific earnings and in (cross-sec tional) occupational mobility. This analysis suggests that it is cost ly to be deficient in English, but the cost is ethnically and occupat ionally specific. Hispanics have a higher cost for English language d eficiency than Asians at every skill level. Copyright 1988 by University of Chicago Press.